THE INFLUENCE OF BRAND CHARACTERISTIC, COMPANY CHARACTERISTIC, AND CONSUMER BRAND CHARACTERISTIC ON BRAND LOYALTY AT BELLAGIO SHOES PRODUCT IN MANADO - Sengkey, Kessy F. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Today's modern society also influences people's behavior in purchasing patterns. Brand has played a role in the modern lifestyle. It is an identity and differentiation of a product that promise to consistently provide privileges, benefits, and certain services to consumers. The research aims to examine and analyze the influence of Brand Trust on Brand Loyalty, Case Study: Bellagio Product in Manado. Data collected through distribution of questionnaires to 60 respondents of Bellagio shoes consumer at Mega Mall and Manado Town Square. The analysis of data in this research using the SPSS. Data test technique is used within the research includes validity test and reliability test. Classical assumption test and multiple linear regression analysis to verify and to prove the research hypothesis. Analysis result demonstrates that Brand characteristic, Company characteristic and Consumer characteristic altogether have a significant effect on brand loyalty of Bellagio shoes product. Therefore Bellagio shoes store Manado is expected to pay attention to increase more the company characteristics since it become a dominant influence on brand loyalty and it can be controlled directly. Keywords: brand characteristic, company characteristic, consumer brand characteritric, brand loyalty